RESPONS PERTUMBUHAN DAN HASIL BIJI KERING KEDELAI EDAMAME (Glycine max (L) Merrill )I DATARAN RENDAH PADA BERBAGAI JARAK TANAM DAN PEMBERIAN PUPUK ORGANIK CAIR - Wibowo Pangestu (Institute of Computer Science (IOCS), 2020)
The objectives of the research was to know the response on growth and production and yield of edamame dried soybean seeds in the lowlands to various plant spacing and the application of liquid organic fertilizer.This research was conducted at Garu VI Medan Amplas street from September until Desember 2019. The research used a Randomized Factorial Group Design, with 2 factor. As the first factor spacing plant of 40 x 20; 30 x 20; 20 x 20 cm and as a second factor Liquid Organic Fertilizer consisting of 40; 60; 80 ml/L. This research results showed that plant spacing treatment significantly affected the number of productive branches. The application of liquid organic fertilizer significantly affected the canopy wet weight and weight of 100 dry seeds.The application of liquid organic fertilizer significantly affected the canopy wet weight and weight of 100 dry seeds. The application of liquid organic fertilizer 40 ml / L markedly increased the canopy fresh weight and weight of 100 edamame soybean seeds. Treatment of 30 x 20 cm spacing significantly increased the number of productive branches of edamame soybeans. The interaction between plant spacing and liquid organic fertilizer treatments did not significantly affect all observed variables.